Optimization of wire electrical discharge turning process: trade-off between production rate and fatigue life - Talebizadehsardari, Pouyan; Eyvazian, Arameh; Musharavati, Farayi; Zeeshan, Qasim; Mahani, Roohollah Babaei; Sebaey, Tamer A. (Springer London Ltd, 2021)
Turning by wire electrical discharge machining (WEDT) has been proven as a successful cutting process for producing complex geometries in difficult-to-cut round bars. However, effects of the process factors on fatigue life and surface integrity have not been studied well. For the first time, in the present investigation it is studied how the WEDT factors influence the surface integrity and subsequent fatigue life of Inconel 718. Experiments were carried out using response surface design taking discharge current, pulse on time, and spindle speed into account as influential parameters. Variation of fatigue life was analyzed and dissuaded by residual stress and surface roughness. Analyses of variance have been taken into account as influential parameters. Finally, a series of optimization results were obtained to understand the trend of fatigue life and material removal rate in Pareto front graphs. Among the obtained results, the one with satisfaction of both responses was compared with the fatigue life and surface integrity of In718 fabricated by the conventional turning process. Results indicated that the fatigue life of parameters at optimum processing conditions (i.e., current of 5 A, pulse time of 1000, and fatigue spindle speed of 250 RPM) can be competitive with finish turning of Inconel 718.
Keywords: Wire electrical discharge turning; Surface integrity; Fatigue life; Parametric influence